The Double Poles Methodology of Islamic Studies Fazlur Rahman - Almahfuz, Almahfuz; Hitami, Munzir; Anwar, Abu (Nurul Jadid University, Paiton Probolinggo, East Java, 2021)
The view of Islamic education in delivering its students to become normative theologically oriented human beings so far has developed, it must redesign its learning methodology to be contemporary modernist, namely trying to continue to strengthen spiritual morals which is a product of the theological pole as well as strengthen scientific knowledge, namely the merging of the two poles. Therefore, it is necessary to study the thoughts of Islamic education thinkers from time to time in the hope that they can be used as material for thoughts, comparisons and references so that quality Islamic education can be realized as a model for general education that has been secular oriented. Fazlur Rahman is one of the originators of contemporary Islamic education thought. he stated that Muslims should be able to combine the two poles of education by integrating secular Western education into Islamic education learning. This thought is known as the Islamization of secular education in the world of Islamic education. So that the pole of empirical knowledge found by practitioners of secular education related to the needs of human life at that time must be accepted and based on the value of religious spirituality